2017
DOI: 10.4067/s0718-48082017000100007
|View full text |Cite
|
Sign up to set email alerts
|

Reducing anxiety, geriatric depression and worry in a sample of older adults through a mindfulness training program

Abstract: this study aimed to analyze the effects of a mindfulness training program on anxiety, worry, and geriatric depression in a sample of older adults. a randomized controlled trial with pretest-posttest measurements was used on an experimental group (n = 42) and a control group (waiting list; n = 45). participants in the experimental group completed the short cognitive examination, the penn state Worry Questionnaire (psWQ), and the Geriatric Depression Scale. Analyses showed significantly stronger reductions in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(42 reference statements)
4
12
0
10
Order By: Relevance
“…This is consistent with previous studies of Meditación-Fluir in which mindfulness was shown to improve state and trait anxiety, depression, and anger regulation in FMS patients ( Amutio et al, 2015a ) and in other populations including adolescents with high levels of aggressiveness and lack of impulse control ( Franco et al, 2016 ) and older adults with high levels of anxiety, depression, and worry ( Franco et al, 2017 ). These previous findings concerning improvements in anger regulation are particularly relevant since the use of adaptive coping strategies to recognize and express emotions has been associated with reduced burden of FMS ( Castelli et al, 2012 ; Geenen et al, 2012 ; Sancassiani et al, 2017 ; Di Tella et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with previous studies of Meditación-Fluir in which mindfulness was shown to improve state and trait anxiety, depression, and anger regulation in FMS patients ( Amutio et al, 2015a ) and in other populations including adolescents with high levels of aggressiveness and lack of impulse control ( Franco et al, 2016 ) and older adults with high levels of anxiety, depression, and worry ( Franco et al, 2017 ). These previous findings concerning improvements in anger regulation are particularly relevant since the use of adaptive coping strategies to recognize and express emotions has been associated with reduced burden of FMS ( Castelli et al, 2012 ; Geenen et al, 2012 ; Sancassiani et al, 2017 ; Di Tella et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The beneficial outcomes observed in the present study were maintained for a minimum of 3 months. Similar maintenance effects have also been observed in other studies of mindfulness involving patients with FMS ( Grossman et al, 2007 ; Amutio et al, 2015a ; Cash et al, 2015 ; Van Gordon et al, 2017 ), as well as in studies following a similar approach to the model of mindfulness training adopted by the Meditación-Fluir intervention used in the present study ( Amutio et al, 2015a ; Franco et al, 2017 ). Some plausible explanations as to why the effects of mindfulness training programs are frequently maintained at follow-up assessments is that mindfulness is a technique that enhances positive affect and that it is relatively easy to integrate into daily life ( Davis and Zautra, 2013 ; Amutio et al, 2015b ; Galvez-Sánchez et al, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition to these four MBIs, the recent mindfulness training program “Flow Meditation” (FM) should also be noted [ 20 , 21 , 22 , 23 , 24 ]; its primary objective is not to try and control thoughts, sensations, or feelings or to modify or change them, but conversely, to allow them to be free, accepting any private event that might occur or emerge spontaneously. FM employs mindfulness breathing, body scan meditation from MBSR, and metaphors and exercises from ACT.…”
Section: Introductionmentioning
confidence: 99%